Under the Veil of Tolerance: Critics on Tolerant City Index - Attaftazani, Muhammad Ikhsan (Fakultas Teologi, Universitas Sanata Dharma, 2023)
Religious tolerance in Indonesia has become phenomenal in the last decades after Setara Institute was established alongside other NGOs such as Wahid Foundation. There is an annual index of tolerant and intolerant cities in Indonesia conducted by the Setara Institute. Other religious indexes are also mentioned, such as the index of Freedom of Religion and Belief (FORB) by Wahid Foundation and the Religious Harmony index by the Ministry of Religious Affairs. This index shows the interreligious relations within society and measures tolerance from the FORB index. To some extent, this index led to the competition of cities in Indonesia to be the most tolerant. This research examines the problem within the index from a philosophical perspective. Furthermore, the effect of the religious tolerance index on local government policies and everyday engagement in society will be addressed. This research uses a qualitative analysis method and collects data through library research. This research shows some problems in the index, such as binary opposition and generalized intolerant action with religious motives. In addition, the tolerance tends to move into pragmatic tolerance instead of mutual tolerance after the index emerges.ABSTRAK Toleransi beragama di Indonesia telah menjadi fenomena dalam beberapa dekade terakhir setelah Setara Institute didirikan bersama dengan LSM lain seperti Wahid Foundation. Setara Institute mengeluarkan indeks tahunan tentang kota-kota toleran dan intoleran di Indonesia. Ada juga indeks keagamaan lainnya, seperti indeks Kebebasan Beragama dan Berkeyakinan (Freedom of Religion and Belief – FORB) yang dikeluarkan oleh Wahid Foundation dan indeks Kerukunan Umat Beragama oleh Kementerian Agama. Indeks-indeks ini menampilkan tingkat hubungan antar agama dalam masyarakat dan mengukur toleransi dari kebebasan beragama dan berkeyakinan. Sampai batas tertentu, indeks ini menyebabkan persaingan antar kota-kota di Indonesia untuk menjadi yang paling toleran. Penelitian dalam makalah ini mengkaji masalah dalam indeks tersebut dari perspektif filosofis. Lebih lanjut, pengaruh indeks toleransi beragama terhadap kebijakan pemerintah daerah dan keterlibatan sehari-hari di masyarakat juga akan dibahas. Penelitian ini menggunakan metode analisis kualitatif dan mengumpulkan data melalui penelitian kepustakaan. Penelitian ini menunjukkan beberapa masalah dalam indeks tersebut, seperti pengandaian oposisi biner yang tidak tepat dan generalisasi atas tindakan intoleran yang dianggap bermotifkan keagamaan. Selain itu, toleransi yang ada cenderung bergeser menjadi toleransi pragmatis dan bukannya toleransi timbal balik setelah adanya indeks tersebut.